Standardization for grand societal challenges - Tartaro, Alessio (Journal of Standardisation, 2024)
The 28th EURAS Annual Standardization Conference, held in Delft, the Netherlands (June 19-21, 2024), explored the multifaceted role of standardization in addressing societal challenges. The conference brought together scholars and practitioners to examine the latest developments in the standardization research and practice. This paper summarizes the key themes discussed during the conference.